Tumor-infiltrating B cells in non-small cell lung cancer: current insights and future directions - Jiang, Shuyue; Zhu, Daxing; Wang, Ye (Cancer cell international, 2025)
Tumor-infiltrating immune cells have been widely recognized as playing an important role in the promotion or inhibition of tumor growth. Recently there has been increasing attention on tumor-infiltrating B cells in the tumor microenvironment. However, the role of B cells in non-small cell lung cancer remains largely unknown. Reviewing recent studies, here we describe the distribution, phenotype, and heterogeneity of B lymphocytes in the non-small cell lung cancer, present their functions and discuss the prognostic significance of the different B-cell subtypes as well as potential therapeutic strategies targeting TIL-Bs. Finally, the review highlights the need for future research to further elucidate their precise function in the tumor microenvironment.